LEADERSHIP MANAGEMENT STYLE AND ACADEMIC STAFF PERFORMANCE OF RIVERS STATE TERTIARY INSTITUTIONS: IMPLICATION FOR POST COVID-19 (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of this research was to empirically investigate the relationship between leadership management style and academic staff performance of Nigeria tertiary institutions with emphasis on post Covid-19 effect. The study applied cross sectional survey design in structured questionnaire to collect data from 400 lecturers of public universities in Rivers State. Spearman’s Rank Correlation Coefficient tool was used with the help of SPSS Version 21.0, to statistically analyzing data obtained from the field. Results revealed that leadership management style has a positive and significant relationship with academic staff performance, however, Covid-19 moderates the extent of relationship between both variables by reducing the impact of the former on the latter. Consequently, the research concluded that analytical leadership is a veritable management tool that when deployed, will improve staff productivity. Therefore, staff performance in universities can be enhanced and measured with high level of productivity through the instrumentality of analytical leadership orientation. Based on the above, the research recommends that government at all levels should apply the analytical leadership orientation, as this research has proven the possibility of enhancing staff productivity and academic performance through this approach.